PHYLOGENY AND SYSTEMATICS OF MULTITUBERCULATE MAMMALS - Kielan-Jaworowska Z.; Hurum J.H. (My University, 2001)
We present a synopsis of high-rank multituberculate systematicsand a manually generated cladogram illustrating multituberculate interrelationships. We divide the Multituberculata into the paraphyletic suborder ‘Plagiaulacida’, an apparently monophyletic suborder Cimolodonta, and one family incertae sedis. Within ‘Plagiaulacida’ we recognise three informal lines: paulchoffatiid (three families), plagiaulacid (three families) and allodontid (two families and the genus Glirodon). The Cimolodonta are divided into an informal Paracimexomys group; three superfamilies: Ptilodontoidea, Djadochtatherioidea (new), and Taeniolabidoidea (restricted to Taeniolabididae); and five families (superfamily incertae sedis): Eucosmodontidae, Microcosmodontidae, Cimolodontidae, Boffiidae, and Kogaionidae; and some genera incertae sedis. New characters used in our analysis are (1) a tendency of molar cusps to coalesce; and (2) ornamentation of grooves, pits, and ridges on the molars. We argue that the Ptilodontoidea, and less certainly also the Cimolodontidae and Boffiidae, might have originated from amongthe plagiaulacid line, a possible intermediate link being the Paracimexomys group. The remaining Cimolodonta might have originated from unknown members of the Paracimexomys group with separated molar cusps and smooth enamel. The origin of two types of prismatic enamel and a relationship between them are stumbling blocks in understanding the origin of the Cimolodonta; we conclude that microprismatic enamel made its appearance only once. Revised diagnoses of high-rank multituberculate taxa, including lists of all known genera, are given.